New Monomeric (CoII, NiII, CuII and ZnII) Metal Complexes of a Bidentate Schiff-base Ligand; Synthesis, Characterisation and Biological Studies - Yousif, Enaam I (Al-Nahrain Journal of Science, 2018)
The new CoII, NiII, CuII, ZnII monomeric complexes with a bidentate Schiff-base ligand [(2-bromo-phenyl)-3-[(2,4-dinitro-phenyl)-hydrazono]-1-methyl-butylidene-amine] L are reported. The ligand L was derived from the condensation reaction of 2,4-dinitrophenylhydrazine and acetylacetone, which then reacted with o-bromoaniline. The complexes were prepared from the reaction of the corresponding metal chloride with the ligand. The ligand and its metal complexes were characterised by spectroscopic methods (FTIR, UV-Vis,1H NMR, A.A), magnetic measurements, chloride content, conductance and melting point. These studies revealed complexes of the general formulae [M(L)2]Cl2 with tetrahedral geometries for CoII and Zn complexes, while square planar geometries have been suggested for NiII and CuII complexes. Biological activity of the ligand and its metal complexes against gram positive bacterial strain Bacillus (G+) and gram negative bacteria Pseudomonase (G-) revealed that the metal complexes become less resistive to the microbial activities as compared to the free ligand.